ENVIRONMENTAL ETHICS IN PAPAL ENCYCLICALS (1981-2020) - Christia, L.Maria; Vijayanand, Dr.A. (The journal of contemporary issues in business and government, 2023)
This paper is an attempt to throw light and understand the environmental ethics mentioned in Papal Encyclicals by the different Catholic Popes according to the sign of the times between 1981 and 2020. They provide precious insights to solve many environmental problems to build up the foundations of environmental ethics. Through the encyclicals, the Popes have touched the hearts of people of various times with eco-concepts. This article exhibits the continuous and creative efforts of the Catholic Church in teaching environmental ethics to every human being who tries to exploit God’s creation due to one’s extravagant needs and greed. Thus, the Church plays a massive role to create awareness among the people of all times to respect and cherish a ‘Green world’.